2018
DOI: 10.11621/pir.2018.0208
|View full text |Cite
|
Sign up to set email alerts
|

Psychological security as the foundation of personal psychological wellbeing (analytical review)

Abstract: Background. Security as a socio-cultural phenomenon requires a comprehensive approach and integrates a multitude of aspects of social reality, each of which is important both for an individual and society as a whole. It has been shown that there are certain universal desires and needs which are valued by all cultures and peoples as essential to providing a high quality of life; one of such universals is the need for security. Consequently, the status of people's security in a society directly depends on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…Furthermore, this study also uncovered how cyberbullying victimization is linked to adolescent depression by discovering that psychological security is a critical mediating factor. The important role of psychological security in terms of individual adaptation has been widely examined [22,23]. According to the cognitive vulnerability model of depression, maladaptive cognition and beliefs regarding self and the world (e.g., low self-esteem and self-worth) are key susceptibility factors contributing to depression [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this study also uncovered how cyberbullying victimization is linked to adolescent depression by discovering that psychological security is a critical mediating factor. The important role of psychological security in terms of individual adaptation has been widely examined [22,23]. According to the cognitive vulnerability model of depression, maladaptive cognition and beliefs regarding self and the world (e.g., low self-esteem and self-worth) are key susceptibility factors contributing to depression [48].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological security refers to the feelings of safety and belongingness, as well as a sense of control over the social environment and confidence in being free from fear [21]. As one of the most important psychological needs, it is the basis of individual well-being and mental health [22,23]. Individuals with poor psychological security may feel rejected and isolated, and further perceive the outer world and other people as threatening, untrustworthy, and uncontrollable [24].…”
Section: The Mediating Rrole Of Psychological Securitymentioning
confidence: 99%
“…The comparative analysis of approaches to the design of psychological assistance for professional and personal development of university students. The comparison was made based on the analysis of the models of psychological assistance and professional and personal development of students functioning in Russian universities, as well as scientific papers covering this issue [2,5,[8][9][10]. The fundamental provisions of the differential acmeological approach were identified using the description method.…”
Section: Methodsmentioning
confidence: 99%
“…Modern youth has the whole range of diverse information available to them, which opens up additional opportunities and simultaneously carries certain risks [1,2]. The non-ranged information can disorient young people and have an ambiguous and sometimes negative impact on their professional and personal development.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological security is the main element that indicates the state of well-being. It"s a dynamic process that reflects on the way people deal with danger and actual threats until well-being emerges (Zotova & Karapetyan, 2018). Bordovskaia & Baeva (2015) have showed that the feelings of happiness, comfort, and protection against diseases and pain are the main indicators for achieving psychological security.…”
Section: Introductionmentioning
confidence: 99%